REVIEW PAPER ON POSITIVE TRAIN CONTROL TECHNOLOGY - Danson Byegon; Birhanu Reesom Bisrat; Kudzai Vushe (International Journal of Innovations in Engineering Research and Technology, 2021)
This review paper focuses on the positive train technology also referred to as PTC (a technology which serves to ensure efficiency, safety and reliability during the train operations in the track) by automatically stopping the train when the train operator seems not to take the required appropriate action when need be, it serves mainly to get rid of accidents caused due to negligence of the train operator or inability to control the freedom of mobility of the train. It looks into the technologies such as Chinese train control systems, Communication based control systems, European train control system all of which can be considered to be part of the Positive train control, other than that, this paper tries to look into what led to creation of this system, the building units and operational layers of a complete PTC system, analyses each unit and its operations and looks further into the challenges affecting the operations of a PTC system try to explore the future trends in this field.